FİNANSAL ARAÇLARIN TMS/TFRS VE BOBİ FRS ÇERÇEVESİNDE MUHASEBELEŞTİRME ESASLARININ KARŞILAŞTIRILMASI - Osman TUĞAY; Kadriye ARISOY (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi, 2019)
Nowadays, the high volume of activities in rapidly changing market conditions increases the effects of financial instruments on balance sheets. Nevertheless, financial instruments are closely interest to both the financial information users within the business and other financial information users (government, investors, credit institutions) who are interested in the business financial statements. In the study, International Accounting and Financial Reporting Standards (IAS / IFRS), the adaptation of our country, Turkey Accounting and Financial Reporting Standards (TAS/TFRS) set in TAS 39 Financial Instruments: accounting and measurement standards, complete with new versions as of 1 January 2018 and after periods the TFRS 9 Financial Instruments Standard and Financial Reporting Standards for Large and Medium Sized Enterprises (FRS for LMEs), which entered into force on 1 January 2018 for businesses that do not implement TAS / TFRS, have been reviewed for financial instruments. The aim of this study is to compare the standards and to better understand the different arrangements with the sample applications.